The Effect of Quercetin Loading in Polylactic Acid-Based Electrospun Fibers on Their Antioxidant, Antibacterial and Antitumor Properties - Nikoleta Stoyanova; Tsvetozara Damyanova; Tsvetelina Paunova-Krasteva; Ani Georgieva; Reneta Toshkova; Mariya Spasova (Molecules)
Quercetin (QUE) is a bioactive flavonoid that is naturally present in various fruits and possesses many pharmacological activities. Despite its health benefits, the bioavailability of quercetin is relatively low due to its crystalline form and hydrophobic structure. An approach to overcoming these drawbacks is its incorporation into amorphous polymer matrices. PLA and PLA/PEG fibrous materials loaded with QUE were obtained by electrospinning. The XRD analysis revealed a visible decrease in the crystallinity of QUE after its incorporation into PLA and PLA/PEG fibers. The obtained fibrous materials and, especially, the PLA/PEG mat loaded with the flavonoid exhibited high antioxidant activity due to the better wettability and higher release rate of the bioactive compound. Moreover, the PLA/QUE and PLA/PEG/QUE mats possessed antibacterial properties against Staphylococcus aureus and Pseudomonas aeruginosa. Furthermore, the antitumor activity of the prepared mats was tested against SH-4 cancer cells and HaCaT keratinocytes. The obtained results reveal that the QUE-loaded fibrous mats exhibited high anticancer activity against cancer cells but lower toxicity to normal keratinocytes. The combined antioxidant, antibacterial and in vitro antitumor activities render these novel PLA-based materials loaded with QUE promising candidates for wound dressing applications and for application in local tumor treatment.